The impact of uncertainty on macro variables: An SVAR-based empirical analysis for EU countries - Ansgar Belke; Dominik Kronen (Research On Money in the Economy (ROME), 2017)
In light of the rising political and economic uncertainty in Europe, we aim to provide a basic understanding of the impact of economic policy uncertainty and financial market uncertainty on a set of macroeconomic variables such as production, consumption and investment. In this paper, we apply a structural vector autoregressive (SVAR) model to gain first insights that may help to identify avenues for further research based on non-linear processes. We find that stock market uncertainty shows a fairly consistently negative effect on the real economy in Europe. However, the implications of economic policy uncertainty for Europe and the Euro area in particular are not so straightforward. It seems as if policy uncertainty raises general investment and consumption of long-lived goods in the EMU core countries in order to be prepared to react on different states of the world in the future. What is more, shifts of invest-ment from peripheral to core EMU member countries as safe havens in uncertain times may produce the same empirical pattern.
Keywords: C32; E20; E60; 330; hysteresis; investment-type decisions; macroeconomic performance under uncertainty; economic policy uncertainty; financial uncertainty; option value of waiting; SVAR